National Symbols as Commemorative Emblems in Nigerian Films - Alawode, Sunday Olayinka; Adesanya, Oluseyi Olufunke; Agboola, Olufunsho Cole (European Scientific Journal, ESJ, 2018)
Nigerian films worldwide are the entertainment offerings of the nation, a burgeoning industry with steady increase growth rate and contributing substantially to the GDP of the nation. National symbols are objects, entities and relics representing an idea, concept, character that may be physical, abstract, religious, cultural, and linguistic among others in a sovereign context and beyond. Symbols or objects that connected together may not have anything in common in reality but by association and common agreement, they have come to represent each other in social contexts; a symbol may arbitrarily denote a referent, icon and index. In the case of Nigeria, the National flag, Anthem, Pledge, Currency, language, Coat of arms, National institutions like the National Assembly complex, Federal Capital Territory (FCT), images of past leaders, historical monuments like the Unknown Soldier (representing military men who died in the cause of protecting the nation), dresses are some of these national symbols. Apart from commemorative historical functions, national symbols are also used to represent hard work, credibility or truthfulness, as well as ethnic differentiation, religious affiliation, cultural background, social status, professional orientation, class distinction among others. Theorizing with Gate-keeping and Framing Analysis, this study adopts a content analysis design which is the study of recorded human communications, an objective and systematic analysis of the contents of any document that are manifest. It is often used to investigate the level of presence of a given content in mass communication. The study selected thirty video films between 2010 and 2015 through a systematic sampling with a random start. Content categories include genre of film, type of symbol, setting of symbol, purpose of symbol, cultural implication of symbol, positioning of symbol, symbiotic relations, prominence, and direction of presentation among others. The study presumed that the nation is replete with communicative, symbolic emblems commemorating historical, cultural, religious, social and family landmarks in nationhood but that these items of symbols are minimally represented in the films that stand as cultural products and identity of the nation in the international community. Findings of the study have dire implications for the critical assessment, representation and image or identity of the nation for the past, present and the future.